Chinese dental students' knowledge and attitudes toward HIV/AIDS - Rui Li; Wenhang Dong; Wei He; Yiming Liu (Elsevier, 2016)
Background/purpose: Oral care is vital to human immunodeficiency virus (HIV)-positive individuals. As future dentists, it is pertinent that dental students have sufficient knowledge and a positive approach toward this disease. The purpose of this study was to assess HIV/AIDS-related knowledge and attitudes among clinical dental students in central China. Materials and methods: This survey was conducted on 103 dental students in the final year of a 5-year program. A structured questionnaire with 50 questions examining their knowledge under various categories and 17 questions examining their attitudes toward the disease was employed. Results: The survey was completed by 92.2% (95/103) of the students. The results revealed that more than half of the respondents demonstrated a good level of knowledge, although few exhibited an excellent level. The mean scores on knowledge was 79.41 ± 6.3 out of a maximum possible score of 100, and there was no significant difference regarding sex. Despite their good level of knowledge, the majority (93.68%) displayed a negative attitude (nonprofessional attitude) toward HIV/AIDS. Conclusion: These findings might help to define strategies to improve the quality of education among Chinese dental students and suggests that there is a need to address student misconceptions and attitudes toward the disease.